Interlayer Engineering of Molybdenum Trioxide toward High‐Capacity and Stable Sodium Ion Half/Full Batteries - Wang, Bo; Ang, Edison Huixiang; Yang, Yang; Zhang, Yufei; Geng, Hongbo; Ye, Minghui; Li, Cheng Chao (Advanced functional materials, 2020)
Orthorhombic molybdenum trioxide (MoO3) is one of the most promising anode materials for sodium‐ion batteries because of its rich chemistry associated with multiple valence states and intriguing layered structure. However, MoO3 still suffers from the low rate capability and poor cycle induced by pulverization during de/sodiation. An ingenious two‐step synthesis strategy to fine tune the layer structure of MoO3 targeting stable and fast sodium ionic diffusion channels is reported here. By integrating partially reduction and organic molecule intercalation methodologies, the interlayer spacing of MoO3 is remarkably enlarged to 10.40 Å and the layer structural integration are reinforced by dimercapto groups of bismuththiol molecules. Comprehensive characterizations and density functional theory calculations prove that the intercalated bismuththiol (DMcT) molecules substantially enhanced electronic conductivity and effectively shield the electrostatic interaction between Na+ and the MoO3 host by conjugated double bond, resulting in improved Na+ insertion/extraction kinetics. Benefiting from these features, the newly devised layered MoO3 electrode achieves excellent long‐term cycling stability and outstanding rate performance. These achievements are of vital significance for the preparation of sodium‐ion battery anode materials with high‐rate capability and long cycling life using intercalation chemistry. Partial reduction and organic molecule intercalation methodologies are developed to fine tune the layer structure of MoO3 targeting stable and fast Na+ diffusion kinetics. Bismuththiol not only expands the diffusion channels for facilitating Na+ diffusion, but also maintains the structural stability as interlayer pillars. In particular, it effectively shields the electrostatic interaction between Na+ and the MoO3 host by a conjugated double bond, resulting in improved Na+ insertion/extraction kinetics.